2024
DOI: 10.20517/energymater.2023.79
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nature-behaviour relationship of carbon black materials for potassium-ion battery electrodes

Sabrina Trano,
Daniele Versaci,
Micaela Castellino
et al.

Abstract: An essential component of a working electrode is the conductive additive: whether it is used in very low amounts or constitutes the conductive matrix, its electrochemical response is not negligible. Commercially diffused carbon black species (i.e., Super P, Super C65, and Super C45) still lack an in-depth electrochemical characterisation in the emerging field of potassium-ion battery systems, which are on the way towards large-scale stationary storage application. Thus, this work aims to provide strong tools t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Consequently, increased research has focused on other alkali-metal-ion-based batteries, such as sodium-ion batteries (NIBs) and potassium-ion batteries (KIBs), because sodium and potassium have more uniform, abundant distribution in the Earth crust compared to a mere 0.0017 wt % , of lithium. Recent studies have suggested several potential cathode materials and low-cost electrolyte salts for NIBs and KIBs that are analogous to those in use for commercial LIBs. However, a suitable anode has yet to be found because Na/graphite and K/graphite compounds may not be thermodynamically stable. Other studies have concluded that the larger radius of the Na-ion (1.02 Å) and K-ion (1.38 Å) compared to that of the Li-ion (0.76 Å) could be the reason for low capacity and poor cycling stability for NIBs and KIBs when graphite is used as the anode. Although recent findings involving other forms of carbon, such as carbon black, microcrystalline structured carbon, and cellulose-derived carbon as electrodes or protective layers for electrodes and those involving the use of emerging polymer , or ionic liquid electrolytes, have yielded promising results in NIBs and KIBs, the search for a commercially viable electrode architecture is far from over.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, increased research has focused on other alkali-metal-ion-based batteries, such as sodium-ion batteries (NIBs) and potassium-ion batteries (KIBs), because sodium and potassium have more uniform, abundant distribution in the Earth crust compared to a mere 0.0017 wt % , of lithium. Recent studies have suggested several potential cathode materials and low-cost electrolyte salts for NIBs and KIBs that are analogous to those in use for commercial LIBs. However, a suitable anode has yet to be found because Na/graphite and K/graphite compounds may not be thermodynamically stable. Other studies have concluded that the larger radius of the Na-ion (1.02 Å) and K-ion (1.38 Å) compared to that of the Li-ion (0.76 Å) could be the reason for low capacity and poor cycling stability for NIBs and KIBs when graphite is used as the anode. Although recent findings involving other forms of carbon, such as carbon black, microcrystalline structured carbon, and cellulose-derived carbon as electrodes or protective layers for electrodes and those involving the use of emerging polymer , or ionic liquid electrolytes, have yielded promising results in NIBs and KIBs, the search for a commercially viable electrode architecture is far from over.…”
Section: Introductionmentioning
confidence: 99%
“… 8 11 Other studies have concluded that the larger radius of the Na-ion (1.02 Å) and K-ion (1.38 Å) compared to that of the Li-ion (0.76 Å) could be the reason for low capacity and poor cycling stability for NIBs and KIBs when graphite is used as the anode. 10 13 Although recent findings involving other forms of carbon, such as carbon black, 14 microcrystalline structured carbon, 15 and cellulose-derived carbon 16 as electrodes or protective layers for electrodes and those involving the use of emerging polymer 17 , 18 or ionic liquid electrolytes, 19 22 have yielded promising results in NIBs and KIBs, 23 25 the search for a commercially viable electrode architecture is far from over.…”
Section: Introductionmentioning
confidence: 99%